Distinction Level of Stress Man Employee and Woman Employee in BNI Syari`ah Bank Padang Subsidiary and The Implication - Rismi, Ridho; Said, Azrul; Zikra, Zikra (Universitas Negeri Padang, 2020)
Work stress in company among others is from the element of the job itself and outside of that job then make stress indication that is observed by physiologic as tired, restless, headache, and easy to get angry then from physicologic aspect as anxiety dissolves, glommy and not consentration and from social aspect as frequently absent, communication not fluent and decision making are bad. This research purposed to deskription and examine how different level stress of man employee and women employee. This research are quantitative research with kind of compratifdeskrption. In this research have an 40 people to become sample of the test. Technique to get sample for this research have general sampling and obtained sample as many 40 employee. Data accumulation use questionnareprosseced by simple deskriptive statistics analys technique for examine different with different test formula. Research results show that first man employee and women employee stress level reviewed by physiologic aspect located on high catagory and very high catagory second man and women employee stress level reviewed by physigologic aspect located on high catagory third man and women employee stress level reviewed by social aspect located on high catagory and the last have an different very significant among man employee stress level between women students. This matter can show from t value more bigger than t table in significant level